Progress and Frontiers of Research on Dexmedetomidine in Perioperative Medicine: A Bibliometric Analysis - Zheng T; Pei Z; Huang X (Drug Design, Development and Therapy)
Teng Zheng,1 Zhi Pei,1 Xiaojing Huang1,2 1Department of Anesthesiology, Shanghai General Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 2Department of Pain Medicine, Shanghai Geriatric Medical Center, Minhang District, Shanghai, People’s Republic of ChinaCorrespondence: Xiaojing Huang, Department of Pain Medicine, Shanghai Geriatric Medical Center, Minhang District, Shanghai, 201104, People’s Republic of China, Email anesthesiahuang@163.comBackground: Dexmedetomidine has received increasing attention for its sedative, analgesic, anxiolytic, anti-inflammatory and anti-stress effects in perioperative medicine. Numerous studies have been carried out to explore its influence on perioperative patients.Objective: This study aimed to identify the most influential literature, trends and hotspots in dexmedetomidine research by bibliometric analysis.Methods: Articles and reviews related to dexmedetomidine in perioperative medicine were collected from Web of Science Core Collection. VOSviewer and Citespace software were used for bibliometric analysis and data visualization.Results: A total of 1652 suitable publications were extracted from the database for analysis, including 1,497 articles and 155 reviews. The number of publications in the field of dexmedetomidine research has increased markedly since 2013, with China being the major contributor, followed by United States. BMC Anesthesiology published the highest number of papers on this topic. Anesthesiology ranked first in terms of average citations per paper and co-citation journal. Ji Fuhai was the most prolific author, and Ma Daqing was the most cited authors. The main hotspots during this period were “elderly patients”, “postoperative cognitive dysfunction”, “injury” and “risk factors”.Conclusion: This study presents an overview of the development related to dexmedetomidine in perioperative medicine using bibliometric analysis. Dexmedetomidine research is thriving and expanding rapidly around the world. The effect of dexmedetomidine on cognitive function has been the latest research hotspot. To advance research in this field, more rigorous and scientific multi-center studies should be designed and further cooperation and academic exchange should be strengthened.Keywords: perioperative medicine, dexmedetomidine, bibliometrics, anesthesia